Certified Kubernetes administrator (CKA) certification training course (Packt Publishing, 2022)
Gain an in-depth knowledge about CKA(Certified Kubernetes Administrator) as well as how to work with Kubernetes in a production environment. About This Video Understand persistent volumes and persistent volume lifecycle Explore Kubernetes pods, deployment, and replica sets Explore the relationship between Kubernetes and containers In Detail Kubernetes is one of the most popular container orchestration tools available. The container orchestration with Kubernetes Certification course will help you grasp the key skills, technology, and concepts that a Kubernetes administrator needs to know. You will learn everything you need to know about Kubernetes. You will start with the very basis of Microservices and the need for it. You will learn about containers and virtualization. Learn and understand the Docker and Kubernetes architecture, understand the Docker swarm features, and learn the difference between Kubernetes and Docker Swarm. Moving further, you will also learn Docker orchestration and the relationship between Kubernetes and Containers. Along the course, you will learn about Kubernetes Pods, deployments and replica sets, persistent volumes, and their lifecycle. You will learn to demonstrate ConfigMap, CronJob, Secret, DaemonSet, label sectors, and more. By the end of this course, you will have gained the knowledge required to design and deploy cloud-native applications on a Kubernetes cluster. Audience This Kubernetes course is best suited for software developers, software engineers, system administrators, Linux administrators, and cloud administrators. Learners need to possess an undergraduate degree or a high school diploma, and a solid understanding of containers and Docker.